British poor schools in the nineteenth century, 1812-1901. - British and Foreign School Society; Catholic Poor School Committee (Great Britain); National Society for Promoting the Education of the Poor in the Principles of the Established Church (Great Britain); Wesleyan Committee of Education (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2016)
These reports cover the history of poor schools and the societies that ran them in Britain. These papers cover schools from the Anglican and Wesleyan denominations as well as secular and Catholic schools. The reports chart the rise of education for the poor from the industrial revolution to the Victorian era. As the number of schools increased, the factory acts released children from work so that they could learn. The effects of these acts can be seen in these papers.
Date range: 1812-1901.
Keywords: Charity schools -- Great Britain -- History -- 19th century -- Sources; Poor children -- Education -- Great Britain -- History -- 19th century